THE SATURATION STATE OF THE WORLD'S OCEAN WITH RESPECT TO (BA,SR)SO - Monnin C.; Cividini D. (My University, 2006)
Barite is commonly found in suspended matter in ocean waters and in marine sediments. The calculation of the barite saturation index of the world's ocean waters has shown that the vast majority of the oceans are undersaturated with respect to pure barium sulfate, equilibrium being reached at a few locations like the Southern Ocean surface waters, deep waters of the Bay of Bengal or intermediate waters of the Pacific [Monnin, C., Jeandel, C., Cattaldo, T., Dehairs, F., 1999. The marine barite saturation state of the world's oceans. Mar. Chem. 65 (3-4), 253-261.]. It is thus paradoxical to commonly find barite in a globally undersaturated ocean. Strontium is the most common impurity in natural barite. It is often suggested that the Ba content of ocean waters is controlled by equilibrium with Sr-substituted barite, and not with pure BaSO4. In order to address this problem, we have used the GEOSECS data (49 stations, 1404 data points) to calculate the saturation index of substituted barite in the world's ocean using Lippmann's description of thermodynamic equilibrium between a solid solution and an aqueous solution for the (Ba,Sr)SO4 system. Recent studies indicate that the (Ba,Sr)SO4 solid solution is most likely regular and continuous. The calculated saturation indices of the regular solid solution (with the interaction parameter A0 equal to 1.6) are closer to those of pure barite than those calculated for the ideal solid solution. Conclusions previously reached for the pure barite case are not changed: the saturation state of ocean waters with respect to a regular solid solution is very close to that of pure barite. Sr-substitution for Ba in barium sulfate does not bring barite at equilibrium. When equilibrium is reached, the degree of Sr substitution of Ba amounts to only a few mole percent of Sr. Equilibrium values of the Sr content of the solid solutions in the intermediate (0.2-0.8) range are found for ocean surface waters where the Ba/Sr ratio is low, but as these waters are undersaturated, such solids are not stable in the water column. This provides another reason for the bimodal distribution of (Ba,Sr)SO4 solid solutions in nature, on top of that induced by the large ratio of the end member solubility products. Equilibrium is found for cold waters (i.e. for temperatures below 5 °C) having a Ba content greater than about 70 nmol/kg. The distribution coefficient of Sr in barite can be calculated from the Ba and Sr concentrations of these samples and from the equilibrium Sr mole fraction of the solid solution obtained from Lippmann's diagram. It was found independent of pressure and it varies only slightly with the temperature of the sample. For the regular solid solution (with A0 = 1.6), it is:{Mathematical expression}This expression (which has been established for temperatures below 5 °C) can be used to directly calculate the composition of solid solutions at equilibrium with a given seawater sample, or conversely to know the Ba content of seawater at equilibrium with a given (Ba,Sr)SO4 solid solution. © 2006.